Model Compounds Used in Research of Coal Conversion and Utilization: A Review - Tang, Yibo; Li, Zenghua; C. Tien, Jerry; Ma, Dongjuan; Yang, Yongliang (Asian Journal of Chemistry, 2014)
Advances in the research of coal chemistry by the model compounds were reviewed. With the development of technology, the molecular-level information of coal was increasingly demanded in studying effective utilization of coal. Comparing with the disorderly and unsystematic organic-groups in the coal, the known functional group in the coal-related model compounds is easier to be traced and measured. As a kind of simplified approach, the model compounds help researchers to understand the details in the processes of coal-related reactions. Unlike the direct investigation on coal, the indagation through coal-related model compounds not only exposits the micro-level variation in typical structures of coal, but also finds out the optimum conditions and influential factors which controlling the whole reaction process. Simultaneously, varieties of possible reaction paths were raised and discussed. Notably, some external additives affect the magnitude and rate of the coal-related model compounds reactions significantly. In the future, the further studies in virtue of coal-related model compounds will continually contribute to the coal industry.